Pengaruh Literasi Bahasa Inggris terhadap Nilai Toefl Mahasiswa - Latif, Dovanda Rahmi; Tri Hapsari, Anggita Dyah; Setiaji, Bayu (Physical Sciences, Life Science and Engineering, 2023)
Globalization has made English is more important than ever. This article examines the effect of English literacy against toefl score by analyzing utbk Literacy utbk scores with toefl score. According to a positive relationship if the utbk literation liteaki is high, then toefl scores are also high. The purpose of this study is to know the certainty of whether the English literacy affects the toefl score. To get how much interest read or English literacy, it is spreading a questionnaire containing 4 questions related to literacy and English, utbk Literacy UKB scores, and toefl scores. 34 Physics Education Studs C Nogyakarta State University Invasion in this study and obtained 74.3% read to 42.9% unlike the English. Based on data obtained on utbk Literacy UKB scores and toefl scores, those who get low utbk scores (<400) also get low toefl scores (± 300). Instead, those who get a high score of the utbk (> 400) also get a high toefl score (> 425) there as well. Students who get a score of utbk > 600 but the lowe the toefl score (<425) so do not pass the test. On the other hand there are students with utbk score (400 450) get a toefl score ± 480. This is certainly there are several factors that cause the phenomenon.